EVALUASI MUTU PENDIDIKAN MELALUI IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DI MIS RAUDHATUL IZZA SUNGAI RUMBAI - Ainun Nur Ja'a; Reni Artika; Muhammad Aji Latif; Rahmad Aditya; Ucelorenza; Gofrinaldo; Widya Dwi Anggraini (STKIP Subang, 2026)
This study aims to describe and analyze the implementation of School-Based Management (Manajemen Berbasis Madrasah/MBM) as an effort to evaluate and improve the quality of education at MIS Raudhatul Izza Sungai Rumbai. The research employs a qualitative case study approach. Data were collected through participatory observation, in-depth interviews with the head of the madrasah, vice-heads, teachers, the madrasah committee, and parents, as well as documentation studies. Data were analyzed through data reduction, data display, and conclusion drawing, with validity tested through source and technique triangulation. The findings indicate that MBM implementation covers seven main components: curriculum and learning management, student affairs, educators and education personnel, facilities and infrastructure, finance, community relations, and special services, although the maturity level varies across components. Quality evaluation using the input-process-output approach shows improvement in learning management and community participation, while constraints remain in facilities, teacher qualifications, and financing capacity. The study recommends strengthening the managerial capacity of madrasah heads, optimizing the role of the madrasah committee, and developing a sustainable internal quality assurance system.